Association between thiol-disulfide hemostasis and transient tachypnea of the newborn in late-preterm and term infants - Mehmet Semih Demirtas; Huseyin Erdal; Fatih Kilicbay; Gaffari Tunc (BMC, 2023)
Abstract Background Transient tachypnea of the newborn (TTN), which is the most common respiratory disease in the neonatal period, increases respiratory workload in newborns. We purposed to evaluate the oxidative stress (OS) status and thiol disulfide hemostasis in late preterm and term newborns with TTN in this study. Methods The study was carried out in a single-centre neonatal intensive care unit to investigate the effect of continuous airway positive pressure (CPAP) on the oxidative system in newborns with TTN. Thiol (native and total) and disulfide levels, total antioxidant and oxidant status (TAS/TOS) and Oxidative stress index (OSI) levels were measured. Results Total thiol levels measured before treatment was 429.5 (369.5-487) µmol/L in the late preterm group and 425 (370-475) µmol/L in the term group (p = 0.741). We found significant changes in TOS, OSI and TAS levels after CPAP treatment in the late preterm group (p < 0.001, p < 0.001, p = 0.012 respectively). It was also found that the disulfide level, which was 26.2 (19.2-31.7) before the treatment, decreased to 19.5 (15.5-28.75) after the treatment (p = 0.001) in late preterms. Conclusion CPAP treatment reduced the OS status burden associated with TTN in neonates. The late preterm newborns with TTN are more affected by OS and increased OS levels decrease with CPAP treatment.